Operation of brillouin fiber laser in the O-band region as compared to that in the C-band region - Ahmad, Harith; Norizan, Siti Fatimah; Zulkifli, Mohd Zamani; Ghani, Zawajer Abd; Harun, Sulaiman Wadi (IOP Publishing, 2011)
A first time O band Brillouin fiber laser is demonstrated and compared with the C band Brillouin fiber laser. By utilizing a 20 km True wave fiber (TWF), the experiment demonstrated four Brillouin lines generated from the simple set-up of Brillouin fiber laser. We compared the threshold between the Brillouin pump wavelength at 1310 nm which represent O band region and 1550 nm for C band region. It shows that the Brillouin threshold at O band region is smaller that C band. The channels spacing between these two bands are also different, where O band have 12.72 GHz spacing while 1550 nm have 10.25 GHz spacing.